THE EFFECT OF BRAND EXPERIENCE AND TRUST ON CUSTOMER LOYALTY THROUGH BRAND ATTACHMENT - Nurul Myristica Indraswari; Tri Ratna Purnamarini; Auliya Rosiana (UPT Publikasi Ilmiah UNISBA, 2026)
This research aims to examine a person’s loyalty to a smartphone brand in terms of the internal stimulus of brand trust and the external stimulus of brand experience. In addition, another goal is to examine the interaction of brand attachment, which plays a mediating role in the relationship between brand experience and brand loyalty, as well as in the relationship between brand trust and brand loyalty. The methodology employed involves collecting primary data through purposive sampling from 195 respondents who have used a specific smartphone brand. The results indicate that brand experience and brand trust significantly influence brand attachment, which in turn contributes to brand loyalty. It also shows that brand attachment mediates both the relationship between brand experience and brand loyalty and the relationship between brand trust and brand loyalty. This research reveals that there has not been a clear enough understanding of the key role of both internal and external stimuli in a comprehensive model to create brand loyalty through brand attachment, based on the Stimuli-Organism-Response (SOR) theory. This research provides important implications for brand managers and the smartphone industry stakeholders in developing an effective marketing strategy to increase brand loyalty and support the achievement of smartphone brand competitive advantages.